INVESTIGATING THE USE OF MULTIMODAL RESOURCES IN LISTENING SKILLS AT JUNIOR HIGH SCHOOL - Atikah, Ade Lia; Gunawan, Muhammad Handi (English Education Department of STKIP Pasundan, 2025)
This study examines junior high school students’ perceptions of the use of multimodal resources in their listening learning experiences, specifically focusing on the integration of video, images, and text. Although, research on multimodal listening is growing, studies focusing on junior high school students’ perceptions of listening activities are limited. This study employs a qualitative case study design involving open-ended questionnaires in the form of students’ reflections, semi-structured interviews, and classroom observations to gather insight into junior high school students’ perceptions and challenges related to multimodal materials in listening instruction. The findings revealed that students had positive views on the use of multimodal resources and the integration of several elements, such as audio, images, and text, can improve their comprehension and engagement in class. On the other hand, challenges such as fast speech speed, unfamiliar vocabulary, and external distractions can hinder their listening comprehension process. To improve teaching, educators should effectively integrate multimodal resources, considering speech speed and the learning environment. In addition, considering students’ perceptions and challenges can help to incorporate multimodal resources more effectively in junior high school environments.